2021
DOI: 10.3390/f12020196
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Taper Functions for Larix olgensis Using Mixed Models and TLS

Abstract: Terrestrial laser scanning (TLS) plays a significant role in forest resource investigation, forest parameter inversion and tree 3D model reconstruction. TLS can accurately, quickly and nondestructively obtain 3D structural information of standing trees. TLS data, rather than felled wood data, were used to construct a mixed model of the taper function based on the tree effect, and the TLS data extraction and model prediction effects were evaluated to derive the stem diameter and volume. TLS was applied to a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…In this study, the extraction accuracy of CRs at different heights was analyzed explicitly with reference to the branch factor data measured in a field containing 30 planted Korean pine trees harvested via destructive harvesting (Table 2). The extraction accuracy was low in the RDINC range of 0-0.15, stabilized from an RDINC of 0.15, and it remained at approximately 91%, which is consistent with the findings of Li [86]. Although trunk diameter extraction was not performed in this study, it was studied in the vertical direction using point cloud data; so, it can be compared with the results of Li's study for mutual verification.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, the extraction accuracy of CRs at different heights was analyzed explicitly with reference to the branch factor data measured in a field containing 30 planted Korean pine trees harvested via destructive harvesting (Table 2). The extraction accuracy was low in the RDINC range of 0-0.15, stabilized from an RDINC of 0.15, and it remained at approximately 91%, which is consistent with the findings of Li [86]. Although trunk diameter extraction was not performed in this study, it was studied in the vertical direction using point cloud data; so, it can be compared with the results of Li's study for mutual verification.…”
Section: Discussionsupporting
confidence: 82%
“…Hook., respectively, but they did not provide specific extraction accuracies because they did not have actual field measurement data for reference. Li [86] et al extracted the trunk diameters of Larix olgensis at different heights in the vertical direction based on TLS data, and they found that the accuracy of the trunk diameter extraction decreased sharply when the relative height exceeded 0.9. In this study, the extraction accuracy of CRs at different heights was analyzed explicitly with reference to the branch factor data measured in a field containing 30 planted Korean pine trees harvested via destructive harvesting (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation